Education of Avanersuarmiut, the Northernmost People in Qaanaaq - Blytmann Trondhjem, Naja (Études Inuit Studies)

(untitled) (Association Inuksiutiit Katimajiit Inc., 2024)
This paper describes how the concept of centre-periphery is linked to modernity, and thus to colonialism and coloniality, by examining the education of non-Kalaallisut-speaking Avanersuarmiut children in Qaanaaq through teaching materials, national tests, and final exams in Kalaallisut, Danish, and English. Within coloniality, the multidialectal perspective is not considered relevant, and the emphasis on the standard language marginalizes local dialects to near extinction. Despite linguistic challenges at the start of schooling, children in Qaanaaq eventually achieve scores comparable to those of Kalaallisut-speaking children. However, due to limited exposure to Danish and English, they obtain low scores in these subjects. When they move to other parts of Greenland for further education, they struggle not only with Danish and English but also with Kalaallisut, facing stigma because of their accent. Despite these challenges, many persevere, supported by second-chance programs that help them eventually complete their education.